Imperial Matter : Ancient Persia and the Archaeology of Empires - Khatchadourian, Lori, 1975- (Book collections on Project MUSE., 2016)
"What is the role of the material world in shaping the tensions and paradoxes of imperial sovereignty? Scholars have long shed light on the complex processes of conquest, extraction, and colonialism under imperial rule. But imperialism has usually been cast as an exclusively human drama, one in which the world of matter does not play an active role. Lori Khatchadourian argues instead that things--from everyday objects to monumental buildings--profoundly shape social and political life under empire. Out of the archaeology of ancient Persia and the South Caucasus, Imperial Matter advances powerful new analytical approaches to the study of imperialism writ large and should be read by scholars working on empire across the humanities and social sciences."--Provided by publisher.